The Borders of Boundlessness: A Reassessment of the Dissolution of Boundaries in in the Contemporary Artworld - Scheller, Jörg (Artium Quaestiones, 2024)
In this article, the early critique of intermedia aesthetics and border-crossing in the arts is reassessed against the background of the contemporary dissolution not only of media boundaries but also of disciplinary, categorical, social boundaries. In 1974, the art critic Rosalind Krauss warned against a trivialization of the dissolution of art’s boundaries in the “post-media condition”. With recourse to Frederic Jameson, she argued that “this leeching of the aesthetic out into the social field in general” ran the risk of mimicking the boundlessness of capitalism. In the same year, Allan Kaprow, the pioneer of happenings, criticized the dissolution of boundaries between video art and entertainment for a broad audience: “Like so much Art Tech of recent years, video environments resemble world’s fair ‘futurama’ displays with their familiar nineteenth-century push-buPon optimism and didacticism. They are part fun house, part psychology lab.” Today, it is worth reconsidering these statements against the backdrop of paradigmatic trends in the post-media condition and the post-modern “explosion of aesthetics” (Gianni Vattimo): inter- and transdisciplinarity, socially engaged arts, artivism, artistic research, critique of the autonomy of art, creative industries... Regardless of their differences, these trends reinforce each other and, particularly in the course of institutionalization and professionalization, may (unintentionally) jeopardize the critical role of the arts at a time when the freedom and autonomy of the arts are under pressure not only from economic capitalization but also from illiberalism, authoritarianism, totalitarianism. In what Belting and Buddensieg have called the art world of the “the global present”, border shifting and border crossing usually have positive connotations, while border formation has negative ones. The autonomy of art implies boundaries that are viewed with suspicion. Yet also for the authoritarian and instrumental mind, the autonomy of the arts is a taboo. There must be no boundary between art and society, or art and politics, or art and economy. With that said, I argue that in order to secure the critical role of the arts in democracies, it is salient to secure their autonomy and to exchange anew ideas about the meaningfulness of not absolute but relative boundaries between categories, disciplines, social systems. This means leaving behind the self-referential rhetoric of dissolving boundaries as something inherently good and re-evaluating the critique of the 1970s in light of the socio-political and economic trends of the present.